Quality Trilogy for Basic Education Administration - Suebsuttha, Rungkarn; Pansiri , Wannaree; Chotientip , Tassanee (Suan Dusit Graduate School Academic Journal, 2025)
In the present day, the world is changing and developing rapidly. Education system is required to undertake the paradigm shift responsive to changes by reviewing and updating existing paradigms relevant to present and future situations by applying the concept of quality trilogy appropriate for the organization context. In addition to, the concept of quality trilogy was one of the quality administration approaches strongly compatible with the present situation of basic education administration. In the age of serious competition, administrators must characterize on self-fulfillment of high competence for reaching goals. The basic educational administration skills of administrators included three essential skills: technical skill was the knowledge and skill related to the use of technology and various applications for improving its operational efficiency. Human skill was regarded as the skill related to communication, teamwork and collaborative learning which was important for building mutual relationships in organizations or work groups. Conceptual skill was the ability to interpret knowledge to suit the situation including analytical thinking and problem solving. This conceptual skill allowed administrators to make operational decisions with confidence and a broader perspective. By applying such skills in conjunction with the quality trilogy management process to develop and increase the quality of basic education, the three management processes consisted of quality planning process for planning and establishing clear and systematic management goals. Quality control process was required for monitoring and controlling work. Lastly, quality improvement process was undertaken to improve the quality of basic education provision for higher quality and efficiency.